PENGEMBANGAN POTENSI JAMUR DI DESA KERU MELALUI PELATIHAN BRANDING, DIGITALISASI PEMASARAN, DIVERSIFIKASI OLAHAN, DAN PEMANFAATAN LIMBAH BERBASIS KEBERLANJUTAN - Patmi, Baiq Olifiya Sri; Wahyudi, Aang; Chandrawati, Yolanda; Cahyani, Pande Ni Ketut Diva Indah; Mbau, Chatrina Elianzari; Rohmaten, Bq Nadiya; Arisandi, Dirja; Huzairi, Ahmad Faqih; Asri, Dewi Agustin; Mawaddah, Erina (Jurnal Wicara, 2025)
Keru Village, Narmada Subdistrict, West Lombok Regency, has great potential in mushroom cultivation, particularly oyster mushroom and merang mushroom cultivation. However, this potential remains limited due to weak branding and digital marketing efforts. To address these issues, the KKN-PMD Keru from Mataram University in 2025 aims to enhance community capacity through product branding training and digital marketing initiatives. Additionally, mushroom potential can be expanded through awareness campaigns and training on mushroom product diversification, nutrition education, and the utilization of mushroom waste (baglog) as organic fertilizer. The methods used are participatory, educational, and practical, involving the community directly in observation, planning, training, practice, and evaluation. The results of the activities showed an increase in community understanding and skills, marked by the formation of a local mushroom product identity, the ability to promote through social media and Google Maps, diversification of ready to-eat products such as mushroom satay and pizza, increased nutritional awareness, especially for pregnant women and infants, and the utilization of mushroom waste into environmentally friendly organic fertilizer. In conclusion, this KKN program successfully supported the strengthening of the local economy based on village potential and promoted the sustainability of community businesses.